Conformational Effects of UV Light on DNA Origami - Haorong Chen; Ruixin Li; Shiming Li; Joakim Andréasson; Jong Hyun Choi (2017)
The responses of DNA origami conformation to UV radiation of different wavelengths and doses are investigated. Short- and medium-wavelength UV light can cause photo-lesions in DNA origami. At moderate doses, the lesions do not cause any visible defects in the origami, nor do they significantly affect the hybridization capability. Instead, they help relieve the internal stress in the origami structure and restore it to the designed conformation. At high doses, staple dissociation increases which causes structural disintegration. Long-wavelength UV does not show any effect on origami conformation by itself. We show that this UV range can be used in conjunction with photoactive molecules for photo-reconfiguration, while avoiding any damage to the DNA structures.